Major problems in Asian American history documents and essays - Kurashige, Lon 1964-.; Murray, Alice Yang. (Boston Houghton Mifflin, 2003)
"Designed to encourage critical thinking about history, the [book] introduces students to both primary sources and analytical essays on important topics in U.S. history. [The book] presents ... selected group of readings in a format that asks students to evaluate primary sources, test the interpretations of distinguished historians and others, and draw their own conclusions"--P. [4] of cover.
Framing Asian American history -- Colonization, Pacific markets, and Asian labor migration to the United States before the Civil War -- The work of national expansion in the American West, 1848-1908 -- Confronting immigration exclusion, 1860s-1920s -- Imperialism and anti-imperialism in the early twentieth century -- Orientalism and popular culture, 1904-1930s -- Interethnic tensions and alliances in the 1920s and 1930s -- Americanization and the second generation, 1920-1942 -- War, race, and the meaning of citizenship, 1941-1988 -- Asian Americans and the Cold War, 1945-1965 -- Post-1965 immigration and Asian America -- Refugees and their struggles in Asia and America, 1975-2000 --Panethnicity, Asian American activism and identity, 1965-2000 -- New formations of Asian American culture, 1990-2001 -- Erasing borders and boundaries : Asian Americans in the twenty-first century.
Includes bibliographical references.
UPV Alumni Affairs Office
Keywords: Asian Americans -- History; Asian Americans -- History -- Sources; United States -- Race relations; United States -- Race relations -- Sources